2007
DOI: 10.1108/11766090710754196
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on Irish financial directors' views about dividends

Abstract: PurposeThis study aims to provide a modern perspective on the role of dividends in smaller developed countries such as Ireland by examining views regarding the determinants of payout levels, the role of taxation and the relevance of conventional signalling theory.Design/methodology/approachThe study employs semi‐structured interviews with the financial directors of 20 leading Irish companies.FindingsThe results suggest support for the notion that dividend policy affects share valuations. However, views regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
0
20
2
Order By: Relevance
“…Yet, significant differences emerged in the perspectives of managers of financial and non-financial firms in this regard. For the non-financial firms, the views of the interviewees contrasts strikingly with the predictions of Lintner's (1956) theoretical model of dividends and the recent empirical findings reported in McCluskey et al (2007). Specifically, all the managers of non-financial firms interviewed in the present study indicated that they are less concerned about setting a target dividend payout ratio; rather, they set their dividends based on current year's earnings.…”
Section: Dividend Conservatismcontrasting
confidence: 87%
See 1 more Smart Citation
“…Yet, significant differences emerged in the perspectives of managers of financial and non-financial firms in this regard. For the non-financial firms, the views of the interviewees contrasts strikingly with the predictions of Lintner's (1956) theoretical model of dividends and the recent empirical findings reported in McCluskey et al (2007). Specifically, all the managers of non-financial firms interviewed in the present study indicated that they are less concerned about setting a target dividend payout ratio; rather, they set their dividends based on current year's earnings.…”
Section: Dividend Conservatismcontrasting
confidence: 87%
“…The semi-structured interview document was piloted on both academics and practitioners, which provided further insight into the appropriateness of the research questions as well as the feasibility of the planned research timeline. The interview guide was designed based on the constructs from previous empirical literature review, including studies by Brav et al, (2005), McCluskey et al, (2007), Baker et al, (2008), Chazi et al, (2011) and Khan et al, (2011). A semi-structured interview is preferred to both the structured and unstructured interviews in this study due to its flexible nature, openness to changes, relatively high face validity and some measure of comparability (Bryman and Bell, 2007;Cameron and Price, 2009;Sekaran and Bougie, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Surveys of executive views on finance issues in the UK, Australia, New Zealand, Singapour, Hong Kong, Indonesia, Thailand, and Ireland have also been carried out. These studies include Kester et al (1999), and Parry (2001), Dhanani (2005), McCluskey (2007. In addition to the above, more recent papers have also been published including those by Troung et al (2006), Butt et al (2010), Mutairi et al (2012), Baker et al (2013), andOzo et al (2015).…”
Section: Dividend Policy: Literature Reviewmentioning
confidence: 98%
“…In his seminal work, Lintner (1956) argued that firms tend to select their dividend level only once they are certain about future earnings and so their announcement reduces uncertainty about future earnings and the market value of a firm (Baker et al, 1985;Baker and Powell, 1999). Many behavioural studies have supported the notion of dividend signalling; for example, McCluskey et al (2007)[5] found that the financial directors of quoted Irish firms were supportive of the signalling hypothesis that dividend and earnings announcement were used to predict future earnings and hence affected the share prices. Similarly, Baker et al (1985)[6] and Baker and Powell (1999)[7] reported firms' belief that dividends can be used as a signalling device to convey information about likely future changes in a firm's share price.…”
Section: Literature Reviewmentioning
confidence: 99%